The evolving role of nation-building in US foreign policy : Lessons learned, lessons lost (Book collections on Project MUSE., 2017)
Now available in paperback, this book explores the processes through which nation-building approaches originated and developed over the last seven decades as well as the concepts and motivations that shaped them. Weaving together International Relations theory and a rich history drawing mainly on declassified documents, interviews and other primary sources, this book contributes to theoretical discussions of nation-building while offering a critique of Realist and Critical Security School analyses of US policy in the developing world. Ultimately, the book illuminates lessons relevant to today's.